Thailand, tryst with modernity - Ghosh, Sucheta. 1949- (New Delhi : Distriutors, UBS Publishers' Distributors, 1997)
20th century politics of Thailand.
PRIORITY 3.
Includes bibliographical references (p. [236]-237) and index.
Keywords: Thailand -- Politics and government